Effect of breading particle size on coating adhesion in breaded,fried poultry - Mohamad Yusof Maskat; William Lloyd Kerr (Universiti Kebangsaan Malaysia, 2002)
Chicken breasts were coated using breading of different particle size. Breading particle size was divided into small (particle size < U.S. No. 60 sieve mesh size), medium (U.S. No. 60 sieve mesh size < particle size < U.S. No. 20 sieve mesh size) and large (particle size > U.S. No. 20 sieve mesh size). Chicken breasts were battered, breaded and deep-fat fried for 240 sec. at an initial temperature of 160oC. The fried products were analysed for coating adhesion, moisture content and yield parameters. Yield parameters measured were coating pickup, cooking loss and cooked yield. Coating adhesion was found to be highest in coating formed from the small particle size breading. Coating formed from the large particle size breading had the lowest coating adhesion. Chicken breasts coated using the small particle size breading showed significantly higher moisture content in the surface region of the chicken meat as well as in the coating. Microstructure of the coatings showed a higher degree of merging between the breading and the batter with decreasing breading particle size. No significant differences were observed in coating pickup, cooking loss and cooked yield between samples coated with different particle size breading.